Shiva linga in the Garbhagriha of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha (sanctum sanctorum) of the Undeshwar Temple is a compact square chamber positioned 2.4 meters below the floor level of the mandapa (pillared hall). Access to the garbhagriha is facilitated by a flight of steps. Positioned at the center of the garbhagriha is a Shiva linga (aniconic representation of Shiva). The walls of the garbhagriha are unadorned and lack any ornamentation or figurative representation.